2017
DOI: 10.1073/pnas.1609000114
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific reorganization of the auditory cortex in deaf humans

Abstract: The principles that guide large-scale cortical reorganization remain unclear. In the blind, several visual regions preserve their task specificity; ventral visual areas, for example, become engaged in auditory and tactile object-recognition tasks. It remains open whether task-specific reorganization is unique to the visual cortex or, alternatively, whether this kind of plasticity is a general principle applying to other cortical areas. Auditory areas can become recruited for visual and tactile input in the dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
123
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 89 publications
(148 reference statements)
7
123
4
Order By: Relevance
“…In these cases, the roles of association sensory cortex regions appear to be defined not by their commonly-driving sensory modality ("visual cortex"), but by their computational role. This was demonstrated in vision (17)(18)(19)(20)(21)(22)(23) for domain selectivity for complex perceptual and functional categories, such as objects, body parts and scenes (23) as well as for functional tasks such as spatial localization (22) and motion perception (24), and has been extended also to functional tasks for audition (25,26). Such selectivity is retained, albeit via different sensory inputs, even in the absence of original dominant sensory experience.…”
Section: Discussionmentioning
confidence: 95%
“…In these cases, the roles of association sensory cortex regions appear to be defined not by their commonly-driving sensory modality ("visual cortex"), but by their computational role. This was demonstrated in vision (17)(18)(19)(20)(21)(22)(23) for domain selectivity for complex perceptual and functional categories, such as objects, body parts and scenes (23) as well as for functional tasks such as spatial localization (22) and motion perception (24), and has been extended also to functional tasks for audition (25,26). Such selectivity is retained, albeit via different sensory inputs, even in the absence of original dominant sensory experience.…”
Section: Discussionmentioning
confidence: 95%
“…In humans, however, there is only limited evidence that specific nonauditory inputs are differentially localized to discrete portions of the auditory-deprived cortices. For example, Bola et al have recently reported, in deaf individuals, cross-modal activations for visual rhythm discrimination in the posterior-lateral and associative auditory regions that are recruited by auditory rhythm discrimination in hearing individuals (5). However, the observed cross-modal recruitment encompassed an extended portion of these temporal regions, which were found activated also by other visual and somatosensory stimuli and tasks in previous studies (2,3).…”
mentioning
confidence: 89%
“…This proposition implies that following hearing loss, auditory areas switch their sensory modality but maintain a relation to its typical function. Following the same thread, another study recently published in PNAS by Bola et al (13) showed an analogous outcome. Using similar groups of deaf and hearing subjects, we explored how the deaf's auditory cortex processes rhythmic stimuli.…”
mentioning
confidence: 59%
“…Overall, these two studies demonstrate that the high-level auditory cortex in the deaf switches its input modality from sound to vision but preserves its task-specific activation pattern independent of input modality (2,13). These findings mean that that task-specific reorganization is not limited to the visual cortex, but might be a general principle that guides cortical plasticity in the brain.…”
mentioning
confidence: 66%
See 1 more Smart Citation